Pendekatan realistic mathematics education untuk meningkatkan pemahaman matematis siswa kelas III Sekolah Dasar pada materi pecahan - Sukma Juliana Rukman; Linda Linda; Ruli Setiyadi (IKIP Siliwangi, 2026)
AbstractThis study examines the effectiveness of the Realistic Mathematics Education (RME) approach in improving elementary students’ conceptual understanding of fractions. The topic is important because many students struggle to connect abstract fraction concepts with real-life meaning. The research employed a Quasi-Experimental method using a Non-Equivalent Control Group Design involving third-grade students, with an experimental group applying RME and a control group using conventional instruction. The results show that RME significantly enhances students’ conceptual understanding, as reflected in the higher posttest average of the experimental group compared to the control group. The t-test results also confirm a significant difference between the two groups. In addition, the N-gain score of the experimental class was higher, and the learning implementation reached the “Very Good” category, supported by positive responses from both students and teachers. These findings indicate that RME effectively bridges abstract concepts with meaningful contexts, leading to improved mathematical conceptual understanding. Keywords: RME, Conceptual Understanding, Fractions. AbstrakPenelitian ini menguji efektivitas Pendekatan Realistic Mathematics Education (RME) dalam meningkatkan pemahaman konsep pecahan pada siswa sekolah dasar. Topik ini penting karena banyak siswa kesulitan mengaitkan konsep pecahan yang abstrak dengan situasi nyata. Penelitian menggunakan metode Kuasi-Eksperimen dengan desain Non-Equivalent Control Group Design pada siswa kelas III, di mana kelas eksperimen menerapkan RME dan kelas kontrol menggunakan pembelajaran konvensional. Hasil penelitian menunjukkan bahwa RME meningkatkan pemahaman konsep secara signifikan, terlihat dari rata-rata posttest kelas eksperimen yang lebih tinggi dibandingkan kelas kontrol. Hasil uji-t turut memperkuat perbedaan signifikan tersebut. Selain itu, nilai N-gain kelas eksperimen lebih besar, dan keterlaksanaan pembelajaran berada pada kategori “Sangat Baik”, diperkuat oleh respon positif siswa dan guru. Temuan ini menunjukkan bahwa RME mampu menjembatani konsep abstrak dengan pengalaman kontekstual, sehingga meningkatkan pemahaman konsep matematis siswa. Kata Kunci: RME, Pemahaman Konsep, Pecahan.